Social assessment for Basilan and Sulu - U.P. Planning and Development Research Foundation, Inc. (Quezon City UP PLANADES, 2002.)
The study serves both as a tool and a process to ensure: a.) that the needs and aspirations of key stakeholders in the area are identified and prioritized; b) recognition and adoption of appropriate and relevant institutional and capacity-building mechanisms for shared partnership and local governance; and c.) formulation and strengthening of open, transparent and sustainable process and methodologies of convergence, coordination and mutual respect. The SA shall seek not only to establish relevance, acceptability and implementability of proposed project components of development programs, but also to install ownership and sustainability of these activities by the local communities of Basilan and Sulu within the context of the formulation of long-term development and rehabilitation plans for the two provinces.
CD-ROM
Keywords: Basilan -- Economic conditions; Basilan -- Social conditions; Sulu -- Economic conditions; Sulu -- Social conditions